BUSINESS DEVELOPMENT STRATEGY OF SHEEP IN CIREBON REGENCY - Fitri Dian Perwitasari; Bastoni Bastoni; Bayu Arisandi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The purpose of this study is to find out what alternative strategies are needed in the development of sheep business that are suitable to be applied in Cirebon Regency, which are expected to have implications for increasing sheep productivity and welfare of farmers. The location of the study was carried out in Cirebon Regency, from March to August 2018. The research method was a survey method to collect primary data from respondents and secondary data. The study sample was determined randomly as many as 43 farmers from three PUSKESWAN regions in Cirebon Regency. Data analysis uses internal environment analysis, external environment analysis, and SWOT analysis. The results of the SWOT matrix analysis are in quadrant II where this stage can grow and be fostered. This business can experience good growth if 1) strengthen the function and role of the group, 2) sheep breeders get continuous guidance and guidance both about the technical, introduction of appropriate technology and marketing from Government Agencies, especially the Agriculture and Livestock Services, Universities and private parties.